Aspects of Experience and Their Role in Systematic Theology - Andersen, John Daniel (Theology and science, 2022)
Experience plays an important role in contemporary theology, but the meaning of the term is often unclear. This article presents six different meanings of the term “experience” and how they are related, inspired by the grounded cognition model of the mind. This is then used to show how the four so-called theological sources (Scripture, tradition, experience and reason) are related in systematic theology. The main argument in the last part is that the four sources produce mental contents which all function simultaneously as conditions when we interpret what the content of Scripture, tradition, experience and reason are.